Ethnobotanical Knowledge on Vegetable Plants Among Traders in Ujungberung Market, Bandung, West Java - Iskandar, Budiawati S.; Mulyanto, Dede; Iskandar, Johan; Yustiadi, Taufik (Media Konservasi, 2023)
Various edible plants, including vegetable are commonly traded in traditional markets of Indonesian cities. Three main objectives of this study: firstly, the elaborate local knowledge of traders on species and landraces of vegetable plants that are traded in the traditional market; secondly the origin supply of vegetable plants that are traded in the traditional market; and thirdly, the utilization of various vegetable plants that are traditionally used as the dietary diversity of the households. The research site was located in the Ujungberung traditional market, Bandung City, West Java. The mixed method of qualitative and quantitative with an ethnobotanical approach was applied in this research. The results of the study showed that based on local knowledge of the vegetable traders, it was documented that total 62 species and landraces representing 18 families of the vegetable plants were commonly traded. While based on a botanical taxonomy, it revealed 48 species representing 18 families. Of the 48 species, 9 species have landraces that are used as vegetable. Various vegetable plants that are commonly traded in the market come from the Bandung and surrounding areas. Traditionally, various vegetable plants are generally used as fresh vegetables and processed into special dishes. The benefit of this research is to development of ethnobotany science aspects, including the influence of human culture on edible plants traded in the traditional market of the cities.